HARTA WARISAN HARUS SEGERA DIBAGIKAN JANGAN DITUNDA - Sri Maharani, M.Pd. (At-Tanmiyah Jurnal Ekonomi dan Bisnis Islam, 2026)
Inheritance Must Be Distributed Immediately, Do Not Delay. In Islam, it is obligatory to immediately distribute inheritance after all conditions are met. Scholars agree that delaying inheritance distribution without a valid reason is haram. Inheritance must be distributed immediately after the obligations related to the heir (debts, wills, funeral costs) have been fulfilled, to maintain justice, avoid slander, and ensure that the rights of each heir are fulfilled according to Islamic law. Delaying inheritance distribution can involve several legal risks that need to be considered, including: potential disputes between heirs, loss of inheritance rights, depreciation of assets, additional costs, tax obligations, injustice and dissatisfaction. The amount of each heir's share has been determined in Islam. If inheritance is not distributed, it will lead to family disputes, prolonged hostility, material losses (loss of goods), legal conflicts, and can even lead to sins (eating assets that are not their right) and tax problems; the resolution can be amicable or through the courts.